MULTIMODAL ANALYSIS ON ADVERTISEMENT OF BODREX EXTRA IN ELECTRONIC MEDIA - Utami Dewi (VISION, 2017)
Multimodality is a theory of communication and social semiotics. Multimodality is a term widely discussed by linguists and semioticians. A wide range of semiotic resources has been used to construct meaning. Multimodality describes communication practices in terms of the textual, oral, linguistic, spatial, and visual resources - or modes - used to compose messages. In this paper, the ads “BODREX EXTRA” in electronic media was analyzed by five semiotic systems of multimodal (sign, symbol and or code). Based on the  analysis of linguistic, visual, audio, spatial, and gestural, it was found there are some of strenghtness and the weakness of the ads BODREX EXTRAMultimodality is a theory of communication and social semiotics.  Multimodality is a term widely discussed by linguists and semioticians. A wide range of semiotic resources has been used to construct meaning. Multimodality describes communication practices in terms of the textual, oral, linguistic, spatial, and visual resources - or modes - used to compose messages. In this paper, the ads “BODREX EXTRA” in electronic media was analyzed by five semiotic systems of multimodal (sign, symbol and or code). Based on the  analysis of linguistic, visual, audio, spatial, and gestural, it was found there are some of strenghtness and the weakness of the ads BODREX EXTRA